Knowledge Regarding Ovarian Cancer among Female School Teachers of Selected School of Western Nepal - Bhatta, Arju; Sharma, Sarojini; Neupane, Laxmi; Koirala, Sushila (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Ovarian cancer is considered a silent killer based on myth, but studies have proved that it shows warning signs and symptoms such as early satiation, pelvic pain, lower back pain, bloating, and abdominal pain, which are of diverse nature, so the symptoms are misapprehended by doctors and women, leading to delayed diagnosis. Method: The study entitled Knowledge on Ovarian Cancer among Female School Teachers in Selected Schools of Bhimdatt Municipality, Kanchanpur was conducted to investigate the school teachers’ knowledge on ovarian cancer. The population of the study was female school teachers teaching secondary-level students. A non-probability purposive sampling technique was used to select the sample, and data were collected through a self-administered structured questionnaire. The study’s sample size was 101. Data were analyzed by using descriptive and inferential statistics. Result: The study’s findings revealed that the respondents’ ages ranged from 21 to 57 years, with a mean age of 36.74±7.748. Regarding ethnicity, 99% were Brahmin/Chhetri, and regarding religion,97% were Hindu. Similarly, in the education level, 44.6% respondents have a master’s degree. The majority of the respondents (93.1%) had a poor level of knowledge regarding ovarian cancer, and 6.9% had a moderate level of expertise. Conclusion: This study concludes that teachers working in schools had a poor level of knowledge regarding ovarian cancer. School teachers are the major stakeholders in the community and can help sensitize women to the early detection and screening of gynecological malignancies.